Indian Economy Documents Library CD : reports, policy documents, discussion papers (New Delhi : Academic Foundation, 2001)
Single CD that contains full-text of a large collection of important reports, policy documents and discussion papers relating to various aspects of India's economy, especially: industry, finance, banking , capital market, infrastructure, agriculture, economic policy & planning.
CD.
rua 10/12/14
Loans
Keywords: India -- Economic conditions; India -- Economic policy